A Modular Approach towards Mesoporous Silica Monoliths with Organically Modified Pore Walls: Nucleophilic Addition, Olefin Metathesis, and Cycloaddition. Issue 13 (13th November 2015) - Göbel, Ronald; Stoltenberg, Marcus; Krehl, Stefan; Biolley, Christine; Rothe, Regina; Schmidt, Bernd; Hesemann, Peter; Taubert, Andreas
Abstract: We have synthesized mesoporous silica (monoliths) with defined surface chemistry by means of a number of addition reactions: (i) coupling of an isocyanate to a surface‐immobilized thiol, (ii) addition of an epoxide to a surface‐immobilized thiol, (iii) cross‐metathesis between two olefins, and (iv) Huisgen [2+3] cycloaddition of an alkyne‐functionalized silica monolith with an azide. Functionalization of the mesopores was observed, but there are significant differences between individual approaches. Isocyanate and epoxide additions lead to high degrees of functionalization, whereas olefin metathesis and [2+3] cycloaddition are less effective. We further show that the efficiency of the modification is about twice as high in mesoporous silica particles than in macroscopic silica monoliths. Abstract : Mesoporous silica monoliths with defined surface chemistry were synthesized by a number of reactions: (i) coupling of an isocyanate to a surface‐immobilized thiol, (ii) addition of an epoxide to a surface‐immobilized thiol, (iii) cross‐metathesis between two olefins, and (iv) Huisgen [2+3] cycloaddition of an alkyne‐functionalized silica monolith with an azide.